2020
DOI: 10.3389/fpls.2020.00742
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Mapping of Loci Associated With Resistance to Clubroot in Brassica napus ssp. napobrassica (Rutabaga) Accessions From Nordic Countries

Abstract: Rutabaga [Brassica napus ssp. napobrassica (L.) Hanelt] is reported to be an excellent source of clubroot (Plasmodiophora brassicae) resistance genes. In this study, 124 rutabaga accessions from the Nordic countries (Norway, Sweden, Finland, Denmark, and Iceland) were evaluated for their reaction to five single-spore isolates representing P. brassicae pathotypes 2F, 3H, 5I, 6M, and 8N and 12 field isolates representing pathotypes 2B, 3A, 3O, 5C, 5G, 5K, 5L, 5X (two isolates, L-G2 and L-G3), 8E, 8J, and 8P. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 69 publications
1
35
1
Order By: Relevance
“…In those previous studies, the disease reaction to only a single strain of P. brassicae was assessed, and a SNP array or associative transcriptome was used rather than GBS, which might explain the difference in the number and identity of QTL detected. In a recent GWAS study, 45 QTLs were identified against 13 strains on chromosomes A01 to A10, and C02, C03 and C05 43 . In the current study, two pathotypes (3A and 2B) included in a recent study 43 were analysed using a larger and potentially more diverse germplasm collection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In those previous studies, the disease reaction to only a single strain of P. brassicae was assessed, and a SNP array or associative transcriptome was used rather than GBS, which might explain the difference in the number and identity of QTL detected. In a recent GWAS study, 45 QTLs were identified against 13 strains on chromosomes A01 to A10, and C02, C03 and C05 43 . In the current study, two pathotypes (3A and 2B) included in a recent study 43 were analysed using a larger and potentially more diverse germplasm collection.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent GWAS study, 45 QTLs were identified against 13 strains on chromosomes A01 to A10, and C02, C03 and C05 43 . In the current study, two pathotypes (3A and 2B) included in a recent study 43 were analysed using a larger and potentially more diverse germplasm collection. The current study, however, identified different QTL from those in the previous study 43 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations